2010
DOI: 10.1177/0042085910377516
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of African American Students’ Attitudes Toward Online Learning

Abstract: The current work presents exploratory research findings concerning African American students’ attitudes toward online learning. The Online Tutoring Attitudes Scale (OTAS; Graff, 2003) was administered to 124 African American students in a positive youth development program. Findings suggest that African American students’ attitudes toward computers are inconsistent with their attitudes toward online learning. African American students reported positive attitudes toward computers; however, their attitudes refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 6 publications
0
20
0
1
Order By: Relevance
“…Results from the same study revealed that minority students' beliefs about their racial identity may be connected to their future educational attainment. Okwumabua, Walker, Hu, and Watson (2011) observed that while the majority of African-American students had positive attitudes toward computers, a significant number did not report high levels of confidence in working online. Other studies such as Ibarra (2000) and Smith and Ayers (2006) found that student groups with a high-context culture, such as Latino students, experienced disadvantages in a web-based learning environment designed with a low-context culture.…”
Section: Diversity Cultures and Online Learningmentioning
confidence: 94%
See 1 more Smart Citation
“…Results from the same study revealed that minority students' beliefs about their racial identity may be connected to their future educational attainment. Okwumabua, Walker, Hu, and Watson (2011) observed that while the majority of African-American students had positive attitudes toward computers, a significant number did not report high levels of confidence in working online. Other studies such as Ibarra (2000) and Smith and Ayers (2006) found that student groups with a high-context culture, such as Latino students, experienced disadvantages in a web-based learning environment designed with a low-context culture.…”
Section: Diversity Cultures and Online Learningmentioning
confidence: 94%
“…As indicated in the literature review, Okwumabua et al (2011) stated that minority students tend to display differently in attitudinal and behavioral aspects of online learning. Second, inequities develop that arise from dominant cultural values embodied in teaching materials and methods (e.g., Gunawardena et al, 2003) and miscommunication among students in online interactions arising from cultural difference (e.g., Wong & Trinidad, 2004).…”
Section: Open-ended Questionsmentioning
confidence: 98%
“…Thus, as an increasing number of minority students continue to enroll in online education (Ashong & Commander, 2012;Petersen, 2015), it is imperative that researchers examine the extent to which instructional strategies such as collaborative learning-well documented in the research literature as effective for the general online student population-works effectively for culturally diverse students. This is particularly important because several studies have reported that instructors of online courses often fail to recognize and address the cultural diversity of their learners in the online learning environments (e.g., Adeoye & Wentling, 2007;Gunawardena, Layne, & Frechette, 2012;Mushtaha & Troyer, 2007;Rogers, Graham & Mayes, 2007), and results from some studies seem to suggest that students from diverse cultural backgrounds exhibit poor leadership skills in leading online discussion (Okwumabua, Walker, Hu, & Watson, 2011), as well as experience challenges in participating online collaborative learning activities (Du & Anderson, 2003). The purpose of this study, therefore, was to investigate the perceptions of culturally diverse graduate students about online collaborative learning activities.…”
Section: Online Collaborative Learning Activities: the Perceptions Ofmentioning
confidence: 99%
“…Previous studies examined differences across cultures (Cronje, 2011;Chew & Yee, 2015;Grandon et al, 2005;Li & Kirkup, 2005;Popov et al, 2012;Popov, Noroozi, Barrett, Biemans, Teasley, Slof & Mulder 2014;Zhu, Valcke & Schellens., 2009) and within cultures (Adler et al, 2001;Chase et al, 2002;Hamdan, 2014;Okwumabua, Walker, Hu & Watson, 2010). In a recent cross-cultural comparison between Malaysian and Australian students, no significant differences in students' perceptions existed on computer usage, lecturer support, equity, student interaction and collaboration (Chew & Yee, 2015).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 99%